PERFORMANCE OF BALI PIGS RAISED IN BAPUK AND CONCRETE FLOOR - K, BUDAARSA; PUGER, A. W.; PUTRI, T. I.; UDAYANA, I D. G. A.; SUDIASTRA, I.W. (Majalah Ilmiah Peternakan, 2018)
This study aims to determine the performance of balimpig by comparing the pig raised in the the bapuk (deep litter) and concrete floor. Each group consists of 10 bali pigs weighing 10-12 kg. The feed given is the same for both groups. Data were analyzed and tested Two Independent Sample T test. The variables measured were feed consumption, weight gain, feed conversion and feed digestibility. The results showed that the average daily weight gain on the bapuk compared with concrete floor were 0.3540±0.0084 vs 0.3680±0.0103 kg (P<0.05), feed conversion 3.2106±0.0796 vs 3.1108±0.0895 (P<0.05), daily feed intake 1.1360 ± 0.0117 vs 1.1440 ± 0.0117 (P>0.05). Dry matter digestibility 79.1840 ± 0.5700 vs 82.0800 ± 1.2518, organic matter 80.6620 ± 0.7633 vs 82.5340 ± 0.5046, crude protein 81.5730 ± 0.8219 vs 83.7310 ± 1.6578, crude fiber 81.5730 ± 0.8219 vs 83.7310 ± 1.6578, crude fat 87.6820 ± 0.8633 vs 89.1800 ± 0.8202 and energy 80.7200 ± 1.0696 vs 81.0620 ± 1.0892 and all digestibility variables in the concrete floor were significantly higher (P<0.05). It can be concluded that the native pig (bali pig) raised in the concrete floor shows better performance in terms of weight gain, feed conversion and feed digestibility.